Teachers’ Acceptance and Readiness to Use Augmented Reality Book to Teach English Vocabulary in Kindergartens - Muryanti, Elise; Pransiska, Rismareni; Novrianti, -; Arkanasya Ummayah, Yasifa; Noer Azhari Azman, Mohamed (JOIV : International Journal on Informatics Visualization, 2023)
English is currently introduced in several Kindergartens in West Sumatra, Indonesia. The focus of introducing English in Kindergartens is introducing simple instruction and vocabulary. The literature review and initial observations show that teaching materials and learning resources to introduce English are still limited. This study aims to explore kindergarten teachers' perspectives on storytelling and using Augmented reality books. This research used a mixing method. The participants in this subject were 57 Kindergarten teachers in West Sumatra, Indonesia. The data of this research was collected through questionnaires and interviews. First, the questionnaire was distributed to explore teachers' acceptance and readiness to use augmented reality storybooks in teaching English vocabulary in a classroom. To validate the data from the questionnaire and interview, they were triangulated. The result shows that most teachers do not have a background in English qualification. They believe that AR can be useful in teaching English vocabulary. Regarding readiness to implement the AR book, the teacher feels optimistic about using the AR stories in the classroom. The teachers believe that AR can motivate children to learn. The respondent teachers accept AR and believe that AR books can benefit children in learning English vocabulary. The ease of using AR and the benefits of AR for teaching vocabulary encourage teachers' readiness to utilize AR storybooks for teaching English vocabulary to Kindergartners. Based on the result of this research, the AR storybook is designed to teach English to Children in Indonesia Kindergarten.